EEG Frequency-Amplitude Characteristics of the Successful Recognition of Emotional Speech - Kislova, O. O.; Rusalova, M. N. (Neuroscience and behavioral physiology, 2010)
EEG frequency-amplitude characteristics were studied in two groups of subjects, with high and low “emotional hearing” measures. Comparison of power over the whole EEG range between the two groups of subjects led to the conclusion that the EEG activation level was significantly higher in subjects with low “emotional hearing” measures than in those with high levels. This group also showed a higher level of activation in the posterior temporal areas of the cortex of the right hemisphere on recognition of emotions in speech. Thus, high initial levels of cortical activation and greater EEG reactivity on hearing emotional phrases are factors hindering the recognition of emotional expression in speech.